Impact of Forced Selection of tRNAs on HIV-1 Replication and Genome Stability Highlight Preferences for Selection of Certain tRNAs - Ni, Na (2006)
Human immunodeficiency virus (HIV-1) exclusively selects tRNA(Lys,3) as the primer for initiation of reverse transcription. How and why HIV-1 selects the tRNA is unresolved. To address this issue, we have generated HIV-1 in which the PBS was changed to be complementary to alternative tRNAs. In this study, we report on HIV-1 that have the PBS mutated to be complementary to tRNA(Thr), tRNA(Phe), tRNA(Ser) and tRNA(Tyr). Virus with a PBS complementary to tRNA(Thr) grew slightly slower than the wild type virus and maintained the PBS for an extended culture period before finally reverting back to utilize tRNA(Lys,3). In contrast, viruses with a PBS complementary to tRNA(Phe) or tRNA(Ser) rapidly reverted to utilize tRNA(Lys,3) following limited in vitro replication, while a virus with a PBS complementary to tRNA(Tyr) had severely compromised infectivity and did not productively infect a continuous T cell line (SupT1) or human peripheral blood mononuclear cells (PBMC). Modification of the A-loop region to be complementary to tRNA(Thr) with the mutation in the PBS to be complementary to tRNA(Thr) resulted in a virus that could stably utilize this tRNA while the modification of the A-loop to be complementary to the anticodon of tRNA(Ser) did not allow the virus to stably utilize tRNA(Ser). Modification of the A-loop region to be complementary to the anticodon of tRNA(Phe) severely impacted the replication of this virus. Finally, the modification of the A-loop region to be complementary to tRNA(Tyr) did not rescue the virus with a PBS complementary to tRNA(Tyr). The results of these studies demonstrate the diverse effects that alteration of the PBS to force selection of alternative primers have on HIV-1 replication and provide a framework to understand the dynamics of primer selection.